Patient-reported outcomes in KEYNOTE-087, a phase 2 study of pembrolizumab in patients with classical Hodgkin lymphoma - Tresckow, Bastian von; Fanale, Michelle; Ardeshna, Kirit M.; Chen, Robert W.; Meißner, Julia; Morschhauser, Franck; Moskowitz, Craig H.; Zinzani, Pier Luigi; Giezek, Hilde; Balakumaran, Arun; Vo, Thao T.; Rauthe, Monika Sabine; et al. (Leukemia and lymphoma, 2019)
In KEYNOTE-087, pembrolizumab had a 69% overall response rate and acceptable safety in patients with relapsed/refractory classical Hodgkin lymphoma (rrHL). We assessed health-related quality of life (HRQoL) in KEYNOTE-087. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (QLQ-C30) and the EuroQoL Five Dimensions Questionnaire 3-level version (EQ-5D) were administered to 206 patients across three cohorts defined by lymphoma progression after: (1) autologous stem cell transplantation (ASCT) and subsequent brentuximab vedotin (BV) (n = 69); (2) salvage chemotherapy and BV (n = 79); and (3) ASCT without post-transplantation BV (n = 58). Compliance/completion rates were ≥90% at week 12 and ≥70% at week 24. QLQ-C30 global health status/QoL and EQ-5D visual analog scale scores showed mean increases from baseline in overall health at all assessed timepoints. With few exceptions, mean improvements from baseline to weeks 12 and 24 in QLQ-C30 functional and symptom scores occurred in all cohorts.Clinicaltrials.gov identifier: NCT02453594.